First-time caller - Borison, B. K. (Borison, B. K. Heartstrings (Series), 2025)
"Aiden Valentine has a secret: he's fallen out of love with love. And as the host of Baltimore's romance hotline, that's a bit of a problem. But when a young girl calls into the station asking for dating advice for her mom, the interview goes viral, thrusting Aiden and Heartstrings into the limelight. Lucie Stone thought she was doing just fine. She has a good job, an incredible family, and a smart, if slightly devious kid. But when all of Baltimore is suddenly scrutinizing her love life-or lack thereof-she begins to question if she's as happy as she thought. Maybe a little more romance wouldn't be such a bad thing. Everyone wants Lucie to find her happy ending... even the handsome, temperamental man calling the shots. But when sparks start to fly behind the scenes, Lucie must make the final call between the radio-sponsored happily ever after, or the man in the headphones next to her"--